Lived experiences of Indonesian nurses working in remote areas: A Descriptive qualitative study - Pardosi, Ivanna Christina; Siburian, Rica Silvia; Silalahi, Vania Naomi; Juniarta, Juniarta; Barus, Novita Susilawati (Journal of Community Empowerment for Health, 2025)
Introduction: Ensuring the equitable distribution of nurses across the region is imperative since they play a crucial role in delivering comprehensive healthcare to individuals, groups, families, and communities. Nevertheless, many regions in Indonesia still face a shortage of nurses, particularly in geographically isolated areas. This study aimed to examine the experiences of Indonesian nurses who were employed in rural areas. Methods: This study used a descriptive qualitative study conducted in mid 2022. Eight nurses with at least one year of experience working in remote healthcare settings, participated in the study. Data was gathered via an online semi-structured interview that lasted between 60 to 80 minutes. The data was transcribed and analyzed using the Colaizzi thematic analysis method. All participants worked in the Eastern part of Indonesia.Results: The present study discovered 73 coding resulting in three major themes and eleven subthemes. Nurses working in rural areas may face challenges that enrich their personal, social, and professional growth. Working in rural areas has enhanced nurses' expertise and creativity.Conclusions: Further investigation is necessary to comprehend the provision and standard of nursing care in rural regions, thereby aiding in the formulation of policies in Indonesia.